Penerapan Standar Global Reporting Initiative (GRI) 200 Pada Laporan Keberlanjutan Perusahaan Sektor Industri Tahun 2024 - Fajar; Indarti Melita Hutagalung; Deanisa Oktavianti (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the level of implementation of the GRI 200 standards in the sustainability reports of industrial sector companies listed on the Indonesia Stock Exchange in 2024. The study used a qualitative descriptive approach with a content analysis method on the sustainability reports of companies selected through a purposive sampling technique. The results show that the level of disclosure of economic aspects of industrial sector companies is still relatively low with a total SRDI value of 0.0683. The economic performance indicator (GRI 201) has the highest level of disclosure, while indicators of anti-competitive behavior (GRI 206) and tax (GRI 207) show the lowest levels of disclosure. These findings indicate that companies tend to prioritize financial economic disclosures and avoid disclosing economic information considered sensitive. This study provides implications for companies and regulators to improve the quality and completeness of economic aspect disclosures in sustainability reports to support corporate transparency and accountability.